Strategi pemasaran BRILink dalam meningkatkan pendapatan Agen - Hero Desyantama; Senna Enzovani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The rapid growth of technology and economic growth is the result of modernization. It is getting easier for people to carry out financial transactions by providing high-quality services as the level of competition between them increases. Banks will make money by providing banking services. Revenue is derived from service-based fees and product revenue. It is hoped that banking services will be able to increase the income of BRILink agents.